Safety and Effectiveness of VYC-17.5L for Long-Term Correction of Nasolabial Folds. (27th July 2019) - Dayan, Steven; Maas, Corey S; Grimes, Pearl E; Beer, Kenneth; Monheit, Gary; Snow, Sean; Murphy, Diane K; Lin, Vince
Abstract: Background: Juvéderm Vollure XC (VYC-17.5L; Allergan plc, Dublin, Ireland) belongs to a family of hyaluronic acid gels based on the Vycross technology platform. Objectives: The authors sought to evaluate the safety and effectiveness of Vollure for correction of moderate to severe nasolabial folds (NLFs) over 18 months and after repeat treatment. Methods: In this prospective, randomized study, patients (N = 123) received initial/touch-up treatment with Vollure in 1 NLF and control filler in the contralateral NLF. Patients received optional repeat treatment with Vollure after month 12, 15, or 18. Assessments included investigator-rated NLF Severity Scale responder rates (≥1-point improvement vs baseline), patient-assessed Appraisal of Nasolabial Folds scale of the FACE-Q questionnaire, and patient satisfaction (11-point scale). Results: Median volume of Vollure injected was 1.7 mL for initial/touch-up treatment combined and 0.6 mL for repeat treatment. The NLF Severity Scale responder rates were 93%, 85%, and 59% at months 6, 9, and 18 after initial/touch-up treatment and increased to 94% at 1 month after repeat treatment. Mean patient-reported FACE-Q scores significantly improved from baseline at all timepoints. Most patients were very satisfied with treatment at all timepoints from day 3 (75%) through month 18 (68%) and at 1 month after repeat treatment (94%). Common injection site responses after initial/touch-up and repeat treatment were firmness, swelling, and tenderness to touch; most were mild/moderate. Conclusions: Vollure was safe and effective for correction of moderate to severe NLFs, with results lasting 18 months in 59% of NLFs. Repeat treatment required one-third of the injection volume to achieve similar improvement in NLF severity as initial/touch-up treatment. Level of Evidence: 2: